Effect of various processing factors on the pH, water activity and microbiological characteristics of pickled Japanese quail (Coturnix c, japonica) eggs - A. Hoover; P.L. Dawson; D.P. Smith; J.K. Northcutt (Journal of Applied Poultry Research)
Summary: This study determined the effect of different commercial pickling errors on pH, water activity and microbiology of hard cooked quail eggs. Experiment 1 tested pH and water activity of cooled and hot hard cooked eggs held for 24 or 48 h in tap water (control) or commercial pickling solution. Experiment 2 examined FDA's 24 h acidification requirement by evaluated egg microbiology after 24 h of storage in commercial brine (5 % vinegar containing 1.5 % sugar (w/v) and 4.3 % salt (w/v)), or in brine missing salt, sugar or both salt and sugar. Hard-cooked eggs were prepared and inoculated in experiment 2 on the peeled surface with a mixed culture of Escherichia coli, Listeria monocytogenes, and Salmonella Typhimurium. A subset of raw eggs was inoculated in the yolk before boiling and surface inoculated. Egg yolk pH and egg albumen pH decreased to 3.9 after 24 h in commercial brine, which is below the pH (4.6) recommended by FDA for safety. Numbers of Salmonella Typhimurium, Listeria monocytogenes, Escherichia coli and coliforms recovered from eggs pickled in commercial brine or brine missing either salt, sugar or both were below the detection limit (< 1.4 log cfu/g egg) after 24 h of holding time. Levels of Salmonella Typhimurium, E. coli and coliforms were detectable on pickled eggs inoculated in the yolk before boiling and surface inoculated after boiling and peeling. This suggests that additional hurdles and environmental monitoring procedures may be needed during quail egg pickling, especially if eggs are suspected to be contaminated by both vertical and horizontal transmission.